Somatic characteristics and efficiency of technical-tactical actions of basketball players at the stage of special basic preparation - Tymanski R.; Smulskij V.; Hucinski T. (Kharkov National Pedagogical University, 2010)
The article deals with an analysis of correlation between the efficiency of technical-tactical actions and some somatic characteristics of APE&S team (Gdansk) basketball players. A close positive correlation between attack action's efficiency with smaller absolute and percentage content of the fat component and with a higher percentage (but no absolute) content of fatless mass has been found. A higher manifestation of defense actions efficiency has been found in the basketball players with more content of fat the component in the body.